2016
DOI: 10.1111/cup.12673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Th2‐ and Th17‐skewed immune phenotype in chronic urticaria with Th22 reduction dependent on autoimmunity and thyroid disease markers

Abstract: These findings provide novel insight into the role of Th2 and Th17 in chronic urticaria pathophysiology and may impact therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…As it is the MC T subtype of mast cells that is particularly associated with allergic disease, this would support an allergic mechanism for CSU. In contrast, other studies found no difference between mast cell numbers in the skin of chronic urticaria patients and healthy individuals …”
Section: Mast Cell Location and Changes In Number In Chronic Urticariamentioning
confidence: 70%
“…As it is the MC T subtype of mast cells that is particularly associated with allergic disease, this would support an allergic mechanism for CSU. In contrast, other studies found no difference between mast cell numbers in the skin of chronic urticaria patients and healthy individuals …”
Section: Mast Cell Location and Changes In Number In Chronic Urticariamentioning
confidence: 70%
“…CD3+ T cells and dual‐labelled cells (e.g. cells with both cytoplasmic CD4+ staining and nuclear T‐bet+ staining) were counted in five consecutive high power fields (HPFs) at × 400 magnification, in a blinded, independent fashion by two of the authors (APM and RMN), as previously described . The number of Th1, Th2, Th17 and Th22 cells as a percentage of CD3+ T cells were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Th17 cells show both inhibitory and stimulatory effects on antibody production by mast cells (6). Of particular relevance to the current study are the recent findings revealing that Th2/ Th17 cytokines, transcription factors and Th2 chemo kines are upregulated or elevated in CSU patients' skin lesions, plasma and serum, respectively (7)(8)(9)(10). Accordingly, Th2 and Th17 pathways may be involved in the pathogenesis of CSU, and CCL17 and IL-17 can serve as serum markers of Th2 and Th17 inflammation, respectively.…”
mentioning
confidence: 63%